Peningkatan Pengetahuan Ibu Nifas tentang Terapy Komplementer Pijat Laktasi di Margadana - Evi Zulfiana; Nora Rahmanindar; Seventina Nurul Hidayah; Diana Safitri (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Breastfeeding is a natural process that is not easy to do. The coverage of exclusive breastfeeding cannot be separated from problems that occur in the breastfeeding process, including the wrong belief that little milk comes out or breast milk is not sufficient for the baby's needs. This situation is caused by several factors including food and drinks consumed by the mother, psychological or emotional conditions of the mother, abnormal breast shape. New methods introduced to prevent and overcome this problem include endorphine massage and lactation massage, massage techniques performed on the head or neck, back, spine, and breast areas that aim to stimulate the hormones prolactin and oxytocin. The purpose of this dedication is to improve the knowledge and skills of breastfeeding mothers in doing lactation massage. The method carried out is to provide training starting with the correct preparation of breastfeeding material. The results of the training that has been given to breastfeeding mothers who attend the posyandu already know and are skilled in practicing lactation massage.